The Dark Side of the Moon. Leadership and Rationalism in the Formulation and Implementation of Educational Policies - Alfredo Rojas Figueroa (Universidad Autónoma de Madrid, 2018)
The last big wave of Educational Reforms in Latin America, begins in the eighties and still in course, has meant numerous investments, with loans of the World Bank and the Inter-American Development Bank that adds several thousands of million dollars into the region. Although Reforms are processes that require several years in completing, their effects are not yet visible. In the present article it is argued that the weaknesses and insufficiencies are the result of of the human action that supposes that educational and the principals in the schools are going to change practices long installed in the daily life, only by mandate. These interpretations supposes that the mandates and the information are "instructive", that produced changes per se, forgetting very important dimensions in the human action and whose consideration would directly lead to give as much importance to the design as to the strategy of implantation of the changes, and that in this strategy, the leadership would play a central rol